2022
DOI: 10.3390/nu14050920
|View full text |Cite
|
Sign up to set email alerts
|

Dietary-Derived Essential Nutrients and Amyotrophic Lateral Sclerosis: A Two-Sample Mendelian Randomization Study

Abstract: Previous studies have suggested a close but inconsistent relationship between essential nutrients and the risk of amyotrophic lateral sclerosis (ALS), and whether this association is causal remains unknown. We aimed to investigate the potential causal relation between essential nutrients (essential amino acids, essential fatty acids, essential minerals, and essential vitamins) and the risk of ALS using Mendelian randomization (MR) analysis. Large-scale European-based genome-wide association studies’ (GWASs) su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Serum LDL-C is a downstream product of the metabolism of PUFAs, and an association between PUFAs and ALS has been suggested previously [43]. Therefore, we further studied the possible mediation effect of LDL-C on the pathway from PUFAs to ALS.…”
Section: Discussionmentioning
confidence: 83%
“…Serum LDL-C is a downstream product of the metabolism of PUFAs, and an association between PUFAs and ALS has been suggested previously [43]. Therefore, we further studied the possible mediation effect of LDL-C on the pathway from PUFAs to ALS.…”
Section: Discussionmentioning
confidence: 83%
“…To investigate the causal relationship for DE-FRGs and DE-ERGs with LUAD, MR analysis was executed to obtain candidate genes by TwoSampleMR function (v 0.5.7) (Xia et al 2022) with P < 5×10 -8 and Inverse variance weighted (IVW) (Burgess et al 2015) was the predominant method. The ieu-a-965 of LUAD was downloaded from Open GWAS database (https://gwas.mrcieu.ac.uk/).…”
Section: Mr Analysis To Obtain Candidate Genesmentioning
confidence: 99%
“…Exposure factors were extracted and filtered using the "extract instruments" function of the TwoSampleMR package (17), with P < 5×10 −8 for forward and P < 5×10 −5 for reverse MR analyses. The initial analysis indicated that, using a strict threshold (P < 5×10 -8 ), the number of IVs was exceedingly limited.…”
Section: Data Pre-processingmentioning
confidence: 99%